Shrek forever after [videorecording (Blu-Ray)] : the final chapter - Mitchell, Mike (Director); Klusner, Josh; Lemke, Darren (DreamWorks Pictures, 2010)
Longing for the days when he was a 'real ogre, ' Shrek signs a deal with Rumpelstiltskin to get his roar back, but turns his world upside down in the process. Donkey suddenly can't remember his best friend, Fiona is now a tough warrior princess, and Puss in Boots is one fat cat! Together, they have just 24 hours to reverse the contract and restore happily forever after. Fourth movie in the Shrek movie series, loosely based on a picture book written by William Steig.